Chemical imaging and assessment of cadmium distribution in the human body. Issue 12 (8th October 2019) - Egger, Alexander E.; Grabmann, Gerlinde; Gollmann-Tepeköylü, Can; Pechriggl, Elisabeth J.; Artner, Christian; Türkcan, Adrian; Hartinger, Christian G.; Fritsch, Helga; Keppler, Bernhard K.; Brenner, Erich; Grimm, Michael; Messner, Barbara; et al.
Abstract : Adipose and muscle tissue – so far underestimated – contribute to the total Cd burden. Cd distribution in testis and kidney correlates with the histologic blood-testis-barrier and renal excretion, respectively. Abstract : The scientific interest in cadmium (Cd) as a human health damaging agent has significantly increased over the past decades. However, particularly the histological distribution of Cd in human tissues is still scarcely defined. Using inductively coupled plasma-mass spectrometry (ICP-MS), we determined the concentration of Cd in 40 different human tissues of four body donors and provided spatial information by elemental imaging on the microscopic distribution of Cd in 8 selected tissues by laser ablation (LA)-ICP-MS. ICP-MS results show that Cd concentrations differ by a factor of 20 000 between different tissues. Apart from the well know deposits in kidney, bone, and liver, our study provides evidence that muscle and adipose tissue are underestimated Cd pools. For the first time, we present spatially resolved Cd distributions in a broad panel of human soft tissues. The defined histological structures are mirrored by sharp cut differences in Cd concentrations between neighboring tissue types, particularly in the rectum, testis, and kidneys. The spatial resolution of the Cd distribution at microscopic level visualized intratissue hot spots of Cd accumulation and is suggested as a powerful tool to elucidate metal based toxicity at histological level.